Can Surgery Be Avoided? Exclusive Antibiotic Treatment for Pelvic Actinomycosis - M. P. Ruiz; E. M. Williams; C. M. Markey; A. M. Johnson; P. B. Morales-Ramirez (Case Reports in Obstetrics and Gynecology)
Pelvic actinomycosis is an uncommon, slowly progressing granulomatous infection that has been associated with the presence of intrauterine devices. Due to its unspecific clinical and radiologic findings, it can mimic pelvic or intra-abdominal malignancy leading to mutilating surgery of high morbidity. Rarely, diagnosis is made preoperatively and in most cases surgical intervention is necessary. The patient in our case is a 42-year-old female with an IUD for 15 years diagnosed with pelvic actinomycosis. Patient was uniquely diagnosed preoperatively through paracentesis and treated conservatively with prolonged antibiotic therapy and without any type of surgical intervention. Follow-up at 1 year showed almost complete radiologic resolution of the inflammatory mass, nutritional recovery, and absence of symptoms. Pelvic actinomycosis can be successfully diagnosed and treated medically without surgical interventions.